Concurrent effects of cold and hyperkalaemia cause insect chilling injury - MacMillan, Heath A. (Proc Biol Sci, 2015)
Chilling injury and death are the ultimate consequence of low temperature exposure for chill susceptible insects, and low temperature tolerance is considered one of the most important factors determining insect distribution patterns. The physiological mechanisms that cause chilling injury are unknown, but chronic cold exposure that causes injury is consistently associated with elevated extracellular [K(+)], and cold tolerant insects possess a greater capacity to maintain ion balance at low temperatures. Here, we use the muscle tissue of the migratory locust (Locusta migratoria) to examine whether chill injury occurs during cold exposure or following return to benign temperature and we specifically examine if elevated extracellular [K(+)], low temperature, or a combination thereof causes cell death. We find that in vivo chill injury occurs during the cold exposure (when extracellular [K(+)] is high) and that there is limited capacity for repair immediately following the cold stress. Further, we demonstrate that that high extracellular [K(+)] causes cell death in situ, but only when experienced at low temperatures. These findings strongly suggest that that the ability to maintain ion (particularly K(+)) balance is critical to insect low temperature survival, and highlight novel routes of study in the mechanisms regulating cell death in insects in the cold.